Identification of peak performance age in track and field athletics - Vobr, R. (International Journal of Performance Analysis in Sport, 2014)
The aim of this paper is to process and evaluate the peak performance age in track and field athletics. The object of this paper is to analyse the top world's Championships (World Championships, European Championships and the Olympic Games) between years 1970 - 2007. Our study is based on status description using normative investigation and developmental survey. Within our investigation we tried to answer questions concerned with significant features of the peak performance age, possibility to state the age accurately, and to monitor its progress. Our data set includes 6314 athletes in total (3,474 men, 2,840 women). Some of the events have binomial distribution which enables accurate peak performance age identification. At present, the age for both sexes moves around 25 and 26 years (except for marathon race). In addition, in long distance races a big disproportion between European and World Championships is found. Surprisingly, there is a difference of 4 years in average in 10 km race. We believe that these results may be of benefit to the individual sport federations, trainers and athletes themselves in their long-term planning of their sport preparation.